The Role of Social Media Marketing in Local SMEs' Products - Kusuma, Annisa Rizka; Yudiani, Ema (Journal of Management, 2024)
Value equity, brand equity, and relationship equity in local MSME products on the Tiktok application are the three aspects of customer equity drivers that this research will use to analyse the impact of social media marketing operations on customer loyalty. Purposive sampling was used with non-probability sampling. 282 users of the Tiktok app who have made local product purchases in Indonesia participated in this poll. In this study, SEM analysis was conducted using SmartPLS 3.0 software and descriptive analysis. The investigation's findings indicate that perceived social media marketing initiatives significantly improve value equity, brand equity, and relationship equity. Customer loyalty is greatly enhanced by value equity, brand equity, and relationship equity